Female–female competition leads to female‐biased sex allocation and dimorphism in brood sex composition in a gall‐forming aphid. (17th December 2018) - Tong, Xin; Akimoto, Shin‐ichi
Abstract: Sex allocation in animals is predicted to be skewed from a 1:1 ratio if sons and daughters yield different marginal fitness returns per unit maternal investment. We tested this prediction using the gall‐forming aphid Tetraneura sorini, in which lethal fighting is common among females, whereas male–male competition is moderate. Mothers (autumnal winged females) parthenogenetically produce females and males in their abdomen and can control their sizes and numbers. The females and males do not feed after birth. After mating, females produce single eggs, from which only females (foundresses) hatch and fight intensely with one another during the galling process. Larger‐sized foundresses have overwhelming advantages in fighting. If mothers invest more in individual females, they can produce larger foundresses (granddaughters), which yields greater fitness returns. This situation is contrary to the original Trivers–Willard hypothesis. Thus, we predicted that more fecund mothers in this species would invest more in females. The cost of producing one female was found to be 3.0–3.2 times the cost of producing one male. Population sex ratios were male‐biased (54.8%–58.2% male), but population sex allocation was highly female biased (68%–72% females). Larger mothers biased their progeny sex ratios more towards females and produced larger females, thus supporting our prediction. Mothers produced two types of brood: all‐female broods and mixed‐sex broods. Mothers with an all‐female brood produced larger females than those with a mixed‐sex brood, thereby offering their granddaughters (foundresses) an advantage in fighting. Local mate competition has been postulated to explain female‐biased population sex allocation in gall‐forming aphids. However, we concluded that competition among foundresses has led to the evolution of female‐biased sex allocation at the population level and dimorphism in brood sex composition. Abstract : Plain Language Summary 营养状态良好的母亲更倾向于生产体型大且强壮的女儿：一个雌性间争斗的蚜虫的案例: 如果母亲可以自由决定后代的性别, 她会做怎样的决定？进化生态学中一个著名的理论（特里弗斯‐威拉徳假说）预测：动物中如红鹿, 雄性间存在争夺配偶的争斗时, 营养状态良好的母亲会将后代性别分配比更偏向于雄性。营养状态良好的母亲可以为她的儿子提供更充足的奶水, 所以儿子可以逐渐发育成体型较大且善于斗争的成年雄鹿。因此, 哺养儿子至一个较大的体型意味着母亲可以通过儿子的繁殖优势获得更大的遗传回报。然而这个理论较难去验证且已有的凭证案例不够充足。这里我们用一个雌性间争斗的造瘿蚜虫为例子来验证这个假说。与一般的哺乳动物不同的是, 在这种造瘿蚜虫中：一龄的雌性幼虫会因虫瘿而展开争斗, 且体型较大的雌性在争斗中具有压倒性的优势；儿子和女儿在母亲腹中发育至最终体型；之后参与争斗的雌性仅拥有母亲提供的营养来发育。以上提到的这些条件非常适合验证这个理论. 实验结果表明, 体型较大的母亲会将后代性别分配比更偏向于雌性, 并生产体型较大的女儿。这个结果明确地验证了特里弗斯‐威拉徳假说。然而, 依旧存在一个问题：就是在种群水平上性别分配比是非常偏向雌性的. 这种非常偏向雌性的性别分配比的现象可以通过考虑蚜虫独特的有性无性世代交替的生命周期来解释。一般来说, 在动物种群中, 后代雌雄性别分配比为一比一。然而, 在同时存在有性无性世代的动物中, 如果在无性世代中雌性间存在争斗, 理论预测在有性世代时, 性别分配比会更偏向雌性。所以, 这个研究不仅验证了进化生态学中的一个重要理论, 还开启了一个新的假说的可能。 【图片说明】 主图为宗林四脉绵蚜 ( Tetraneura sorini ) 的虫瘿。右上方为玻片封固标本中的有性雌虫与雄虫。右下方为一龄干母幼虫, 其会诱导产生虫瘿并频繁与其他一龄幼虫进行争斗。 A plain language summary is available for this article.